BALINESE WOMEN IN SPA TOURISM IN BADUNG REGENCY - Osin, Rosvita Flaviana; Pibriari, Ni Putu Widhya; Anggayana, I Wayan Agus (International Conference on Cultural Studies, 2019)
This study aims to overview the existence of women in Badung Regency who work in the Spa industry and find out the economic, social and cultural roles and implications who work in the Spa industry. This study uses quantitative and qualitative data. The technique of data collection is done through informant interviews, observations, and questionnaires. The results showed overall of 20 spa therapists 85 percent had revealed that they experienced an increase in quality of life after working in the spa industry. Balinese women in the Spa industry have strength in terms of friendly, smiling, honest attitude and high work skills. Its weaknesses include lower English language skills, low motivation to occupy positions, lack of confidence, lack of competency certification. The job opportunity is very high, Bali's tourism potential, Spa is a promising industry, has high priority. Threats faced are changes in consumer tastes and business competition. The role and implications of Balinese women working in the Spa industry (a) economic implications of Balinese women being able to help families to increase family income. (b) The social implications of Balinese women being able to improve their social status themselves and their families. (c) cultural implications of Balinese women being able to preserve their culture.